PENGARUH PENAMBAHAN MINYAK VCO (Virgin Coconut Oil) DALAM FORMULASI SEDIAAN MASKER CLAY ALFA-TOKOFEROL SEBAGAI ANTI-AGING - DOLOKSARIBU, FERIDAWATY; SURYANO, MONICA (Jurnal Farmanesia, 2022)
Antioxidants are molecules or compounds that reduce the activity of free radicals by preventing cell oxidation which can be used as anti-aging or preventing premature aging. Vitamin E and lauric acid and oleic acid from VCO oil as antioxidants that can protect the skin from free radicals and which work as moisturizers to prevent dry skin. The purpose of this study was to formulate and evaluate clay mask preparations from alpha-tocopherol and VCO oil as anti-aging. The clay mask preparation was formulated using bentonite, xanthan gum, kaolin, glycerin, sodium lauryl sulfate, titanium dioxide, nipagin, BHT, distilled water, perfume and with the addition of alpha-tocopherol and VCO oil with concentrations of 1%:5%, 1, respectively. %:7%, and 1%:9%. Tests on clay mask preparations include homogeneity test, stability test, pH test, irritation test, mask drying time test and measurement of anti-aging effectiveness using a skin analyzer on volunteers' faces. The results of the treatment carried out for four (4) weeks got better with increasing water content (22.33 to 40.66), pore size getting smaller (39.66 to 20.00), stains getting smaller (40.66 to 21 ,00), wrinkles are decreasing (34.00 to 16.00). The conclusion of this study is that alpha-tocopherol and VCO oil can be used as anti-aging in clay mask preparations, meet the quality requirements of the preparation and do not cause irritation during use and provide a good anti-aging effect for four (4) weeks of treatment.